Digital television policy in Ireland: From inception to analogue switch off. (1st June 2013) - Murphy, Kenneth
On 24 October 2012 the Republic of Ireland switched off its analogue spectrum marking a crucial juncture in its transition to a fully digital television system. After fourteen years of policy-making, the Irish state had met both its digital switchover and analogue switch off deadlines. This article will trace the long trajectory of Ireland's transition to digital television and evaluate the state's policy performance in the much-changed context of digital media governance. Amongst the myriad policy goals that were incorporated under the rubric of digital television policy (information society goals, network development goals, television policy goals) successive governments achieved some policy goals but not all. In Ireland the signal policy failure has been in relation to the late launch and compromised model of digital terrestrial television (DTT). Whereas there are varied factors and contexts that have shaped Ireland's digital transition the article will trace the part played by Ireland's negotiation of EU governance in this area and Ireland's own state structure and its implication for policy-making at critical points in Irelands' digital transition. The Irish state's status as a competition state engendered a policy approach that frequently became wedged between the twin pressures of interest group manoeuvring and the EU's evolving approach to governing state aid towards DTV.